Arte e loucura: uma questão contemporânea - Lacerda, Elizeth Tavares de (1997)
This dissertation points to an experience developed in a psychiatric institution, the IPUB/UFRJ, and their unfolding in the community with a view to situate the creational process related to the madness in the nineties years. This work is divided in three moments: the first one, turns its attention to the theoretical knowledge about art and madness. The second goes back and makes an survey on the medical recors of patients treated in the old national "asylum" using the medical appointment, between the years of 1896 to 1906, through the doctor's view and the "alienated" patients and their speech. And the third moment, discusses "art and madness", through the medicine perception of the psychiatric patient and people in the community.